Improvement of the potability of surface water by using the filtration method - Malema, Mokaba Shirley (My University, 2016)
Access to safe drinking water is a major problem globally and it mostly affects people living in low-income countries. The lack of potable water leads to the use of raw water from surface or ground water sources for drinking and other household purposes. A water filtration unit was designed and constructed using fabric, gravel and sand, which were wet-packaged into a 20 L bucket. The efficiency of the filter unit to improve the bio-physicochemical properties of contaminated water was tested using surface waters from rivers in the Sekhukhune area. Physico-chemical parameters tested included turbidity, colour, total suspended solids (TSS), total dissolved solids (TDS), total hardness and pH. Turbidity and colour were the most improved characteristics, where turbidity improved by 69% and colour by 80%. Other parameters such as total hardness, TSS and TDS were non-significantly reduced following treatment with the filtration unit. The amount of soluble solids in raw water was well within allowable limits by WHO standards. Microbiological tests included heterotrophic bacteria, total coliform and faecal coliform counts. The bacterial load was too numerous to count for the untreated water, however, after treatment with the filtration unit, heterotrophic bacterial load decreased to 15 x 10103 CFU/ml, total coliforms to 14 x 10 2 CFU/100ml and faecal coliforms to 11 x 10 2 CFU/100ml. Further treatment with UV sterilization unit resulted in undetectable amount of bacteria. The unit designed in this study can be beneficial in those rural communities were clean water is not available, it is easy to construct and simple to operate and most importantly it reduced contaminants in surface water. The UV unit incorporated in this study is not cost effective, therefore, other household treatment options such as chlorination and boiling which are easily accessible to most communities can be used to further eliminate remaining microorganisms after filtration. The effective shortest boiling time and minimum dosage of Na(OCl2) have been previously tested in our laboratory and total elimination of bacteria was achieved within 2 minutes of rolling boil and after 30 minutes following addition of 5ml/20L of liquid chlorine.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2016
Keywords: Water filtration-unit; UV sterilization unit; Bio-physicochemical properties; River water; Water -- Purification -- South Africa -- Limpopo; Water -- Purification -- Filtration; Sedimentation and deposition -- Research